Dasar penempatan-pertukaran, kompetensi, dan tanggungan tugas dalam perkhidmatan guru di Sabah dan Sarawak / Esmali Bari - Esmali , Bari (2017)
School teachers are the major human resource in the education sector because they conduct and implement the instructional process in classrooms, and the quality of an education system cannot exceed the quality of its teacher (Barber & Mourshed, 2007). The aim of this study was to determine strategies used by school administrators to deal with matters relating to the placement and transfer of teachers in Sabah and Sarawak. The study also attempted to gauge teachers‘ competency level and their various responsibilities in the two states concerned, which had to address the issue of having a high number of under-enrolled schools in remote areas and low quality schools. This study employed a survey method, which was carried out in two phases: Phase I investigated the placement and transfer policy of teachers, with respondents consisting of 268 school administrators; and Phase II investigated teacher competencies and responsibilities with a sample size of 785 teachers. The respondents were selected through a combination of stratified, cluster, and simple random sampling. In Phase I, the questionnaire had three sections, including some open-ended questions. In Phase II, the questionnaire had five parts. Through the results of the pilot study, the internal reliability of the instrument was found to be in a reasonable range, namely α = 0.85 - 0.94. Data was analyzed using descriptive statistics, Multiple Response Analysis, and ANOVA. Results indicated that the school administrator believed that the subject major was the main factor considered for teacher placement and transfer. Subsequent factors such as family, health and quality of service were also some key considerations in teacher transfer. Through Confirmatory Factor Analysis, the study confirmed that there were seven subconstructs in professional competence of teachers. Exploratory Factor Analysis showed that there were four subcontructs in teacher responsibilities. Generally, all teachers had high level of professional competence. However, experienced teachers teaching more than 16 years, primary school teachers, teachers with Professional Certificate in Teaching, and male teachers, all show higher levels of competence than other variables in particular subconstructs. All teachers from different demographic backgrounds agreed that the main task of the teacher is performing teaching activities. However, a major portion of their time included carrying out school management tasks and co-curricular related activities. Difficult terrain and limited school facilities in Sabah and Sarawak posed a major challenge in implementing teacher placement and transfer policy in Sabah and Sarawak. Therefore, to improve the quality and condition of teachers in these states, stakeholders in the education system should consider aspects such as school infrastructure, education resources facilities, teachers‘ expertise, quality of teachers, teaching and learning practices, SKM management, teachers' welfare, lesson duration, and local views of ethnic groups.